FACTORS AFFECTING ETHICAL LEADERSHIP OF BASIC EDUCATION SCHOOL ADMINISTRATORS UNDER THE OFFICE OF THE BASIC EDUCATION COMMISSION: A STRUCTURAL EQUATION MODEL - Choojeen, Kanyamas; Phuangsomjit, Choochat; Angsuchoti, Supamas; Sukapirom, Rungrouang (PEOPLE: International Journal of Social Sciences, 2017)
The purposes of this research were (1) To study ethical leadership, internal and external factors of the school affecting ethical leadership; and (2) To study the influences of internal and external factors of the school affecting ethical leadership. The research sample consisted of 215 basic education school administrators. The employed research instruments were a form containing guidelines for in-depth interviews, and a 5-scale rating questionnaire. Research findings:(1) It was found that five aspects of ethical leadership, namely, having good discipline, behaving as a good model, Leading the proper way of life, love and faith in the profession, and professional responsibility. And it was found internal and external factors of the school affecting ethical leadership, namely, having a prototype model person, ethical enhancement from social institutions, ethical enhancing social environment, characteristics fostering ethical development, having ethical oriented atmosphere, having the practices based on social norm, having ethical oriented organizational culture, and having ethical-based reward and punishment system.(2) The influence of the internal factors was a little higher than that of the external factors of the school.